The effects of poverty evaluated based on the integration of human needs as stipulated in maqasidalsyariah and maslow's hierarchy of needs on zakat distribution efficiency / Maheran Zakaria ... [et al.] - Zakaria, Maheran; Awang, Suryani; Nik Abdulatiff, Nik Kamaruzaman; Samba Mohamed, Nor Hayati (Accounting Research Institute, 2014)
The objective of this study is to investigate the effects of poverty evaluated based on the integration of human needs as stipulated in the perspective of Maqasid al- Syariah and Maslow's Hierarchy of Needs on zakat distribution efficiency. Approximately 450 sets of questionnaire were personally sent to zakat recipients of two programs conducted by Majlis Agama Islam Kelantan (MAIK) namely business assistance and living skill course. From this amount, 420 people responded, amounting to 93.33 % response rate. Data were analyzed using Social Science Statistical Package (SSPS) 20 and Analysis of Moment Structure (AMOS) 20. From the findings, it can be concluded that poverty evaluated based on the integration of human needs as stipulated in the perspective of Maqasid al-Syariah and Maslow's Hierarchy of Needs positively affects the efficiency of zakat distribution. Hence, the study provides an insight to zakat institutions, policy makers and the public of the importance of these multi-dimensional factors in evaluating poverty in relation to the efficiency of zakat distribution.